Spatial distribution of polycyclic aromatic hydrocarbon and polychlorinated biphenyl sources in the Nakdong River Estuary, South Korea. Issue 12 (15th October 2017) - Lee, Jun H.; Woo, Han J.; Jeong, Kap S.; Kang, Jeong W.; Choi, Jae U.; Jeong, Eun J.; Park, Kap S.; Lee, Dong H.
ABSTRACT: Our research team investigated the elemental composition and the presence of various toxic organic compounds, such as polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs), in estuary surface sediments to trace the spatial distribution of the sources of pollution deposited in Nakdong River, Busan, South Korea. The spatial patterns of elemental composition and toxic organic compounds were determined from the measurements of total organic carbon (TOC), total nitrogen, total sulfur, PAHs, and PCBs. The sediments had TOC contents of between 0.02 and 1.80 wt% (avg. 0.34 wt%), depending on the amount of clay-sized particles. The concentrations of PAHs and PCBs (10.8–167.7 ng g −1 dry wt and 197.0–754.0 pg g −1 dry wt, respectively) in surface sediments revealed different spatial patterns for these compounds, suggesting that they partially originated from the combustion of fossil fuels and from the use of commercial PCB products at adjacent industrial complexes. Although these concentrations were far below the Sediment Quality Guideline (SQG) of the National Oceanic and Atmospheric Administration (NOAA), the sediments at one site contained PCBs at concentrations close to the response level (754.0 pg g −1 dry wt), and were dominated by low-molecular-weight PAHs. The PAHs and PCBs in Nakdong River Estuary sediments were likely to have originated from the combustion of fossil fuels and biomass at the adjacent industrial complexes. The primarily analyzed results determined that PAHs originated from the combustion of fossil fuels and biomass, and overall concentrations were related to the contributions of individual PAHs in most sediment samples. Based on the SQG of the NOAA, our results indicate that the anthropogenic activity should be considered on the future-sustainable management of this estuary system.